Shyara's De Apam Balique / Natashya Amyra Maula Azmi - Natashya Amyra, Maula Azmi (2020)
Shyara's De Apam Balique is a business that provides various flavour of apam balik. In these days, people tend to demand products that have variety of flavour and products that are rare to be in the market. Our shop provide variety flavour of ‘apam balik’ such as nutella with oreo, nutella with nestum, nutella with strawberry filling, nutella with banana, cheese with blueberry, cheese wih corn, cheese with peanut and cheese with nutella. Our main target market are teenagers, adults and families. To make it clear 50% of our target market are for teenagers, 30% for adult and 20% goes to families. Firstly, 50% of teenagers will come to our shop because they like to eat something that is sweet and tends to try something new in their life. Secondly, 30% of target market are goes to the adults. Lastly, 20% of the families will come to our shop in the weekend to spend time and enjoy the delicious of our ‘apam balik’ with their family members. Next, our shop offered product to our customer by giving the best deal compared to other competitor. This is because our shop offered variety of promotion such as selfie contest with 'apam balik', vouchers and others to attract them to buy product in our shop. By this way, they can purchase our product at lower price or even get it free by joining our selfie contest with 'apam balik' or get the discount of 'apam balik' from us. Other competitors does not brave enough to take a risk like what our shop do. So this is a chance for us to gain a lot of customers by doing some promotion in our shop. Our shop also targeting to gain more profit every year. We target to achieve about more than RM 900 000 for the second year. More, Shyara’s De Apam Balique marketing strategies are introducing the ‘apam balik’ in the website or application with a great marketing by providing interesting information and facts about ‘apam balik’ and our shop. More, we will provide business card of our shop for any reservations of events or functions. Other than that, we will also provide store number for our customer. This will make our customer feel free to contact us to make any reservation in our shop.